Interactive online book system - Bindu Priya, P; Rohit, G; P.S.G.Aruna Sri, Mrs (International Journal of Engineering and Technology, 2018)
The basic objective of making interactive book system is to make a web application. Which serves individuals with each one of the functionalities gave in a book shop. Few conditions are taken as consideration to developing this application, first one is customer view and second one is administrative view. In customer view customer can upload the book and download a book and they can add the anno-tations to know about the book. They can provide the suggestions about that book. That can be viewed by administrator and admin can solve as per the instructions. The architecture of application is plot both the customer view and administrative view. Administrator has to verify customer identity by this application. This application is processed by JAVA programming language, For designing we are using HTML and CSS.